Von Willebrand factor antigen in systemic lupus erythematosus and antiphospholipid syndrome - A A Novikov; E N Alexandrova; T V Popkova; T M Reshetnyak; N G Klyukvina; D S Novikova; LB Slitivelband; A A Baranov (Научно-практическая ревматология)
To study clinical significance of von Willebrand factor antigen (WFA) in antiphospholipid syndrome and systemic lupus erythematosus (SLE). Material and methods. Serum concentration of WFA was determined with immune-enzyme assay in 21 pts with primary APS (PAPS), 39 SLE pts with APS, 68 SLE pts and 56 healthy donors. Results. WFA level in PAPS, SLE+APS and SLE was significantly higher than in donors. WFA concentration in serum of SLE pts without APS significantly exceeded that in PAPS. WFA concentration elevation was revealed in 52,4% of PAPS, 56,4% SLE+APS and 73,5% SLE pts. There was no association between WFA level, thromboses and obstetric pathology in PAPS and SLE. WFA concentration increase in SLE with APS correlated with IgM anticardiolipin antibodies and SLEDAI activity index (p<0,05), in SLE - with SLEDAI and ECLAM activity indices (p<0,05). WFA level in SLE pts with renal disease was significantly higher than in SLE pts without renal disease. There was a direct correlation between WFA level and ESR (p<0,05) so as with CRP (p<0,05) in SLE. There were no significant differences of WFA level in SLE pts with and without atherosclerotic plaques. WFA level did not correlate with intima-media complex thickness. Conclusion. Development of immunopathological processin SLE and APS is associated with WFA hyper production. WFA elevated level reflects inflammatory activity of the disease in SLE but is not associated with presence of thrombotic and atherothrombotic complications in APS.